A qualitative analysis of movement characteristics in success and failure of aerial maneuvers based on torso orientation in professional surfing - Chun, S.; Park, J. C. (International Journal of Sports Science & Coaching, 2025)
One of the keys to success in competitive surfing is mastering aerial skills. Aerials, performed both frontside and backside, should have their movement characteristics examined to identify what contributes to success or failure across a variety of performance levels. In this study, 2554 rides from in competition videos of the World Surf League's 2021-2022 Championship Tour and Challenger Series were analyzed. Frontside-air-reverse (FAR) emerged as the most frequently used maneuver at frontside, and backside-air-reverse (BAR) at backside. The study included 42 male surfers. Evaluated based on 40 distinct movement characteristics, and each maneuver's success or failure were classified. The key movement characteristics for successful FAR include rotation initiated, excessive foot movement, trail valgus presents in landing, width of stance greater than shoulder width, center of mass is located over nose board at initial contact, chest over lead knee, trunk flexion over 45 degrees from vertical, lead arm over toeside rail, trail arm over toeside rail, favour the toeside rail. In BAR, trail arm over toeside rail was confirmed. These results demonstrate movement characteristics for successful aerial skill performance in a various surfing population to frontside and backside. Understanding the movement characteristics that contribute to success or failure can improve athlete performance and contribute to more scientifically based coaching.